Antioxidant Activity Test for Rukam Fruit (Flacourtia rukam) Of Maseration Extract - Inas Fadiyah; Iin Lestari; Shelly Victory (Stannum : Jurnal Sains dan Terapan Kimia, 2019)
Rukam fruit (Flacourtia rukam) is one of the wild plants that are widely distributed in Indonesia, especially on the island of Bangka. The results of previous studies stated that rukam fruit has a phenolic content of 40 mg GAE / 100 grams. Phenolic compounds have major benefits as antioxidants, where antioxidants have the ability to inhibit the work of free radicals. Therefore a study was conducted to assess the content of secondary metabolites and the antioxidant bioactivity of the Flacourtia rukam species using maceration method. Rukam fruit extract was obtained using the Maceration method. As for the antioxidant test using the DPPH` method. The results of the antioxidant activity test of rukam extract with ethanol solvent obtained IC50 value 236,169 µg / mL and in rukam extract with acetone solvent obtained IC50 276,443 µg / mL which showed that the antioxidant properties of this rukam were moderate.